Optimization of manufacturing process for serotype 14 pneumococcal capsular polysaccharide - Li, Yuelong; Xu, Yongxue; Cao, Xin; Wang, Yanyan; Wang, Jianlong; Zhao, Yi; Wang, Hui; Yao, Hantian; Liu, Jiankai (Frontiers in Chemical Engineering, 2024)
Streptococcus pneumoniae is a pathogenic bacterium that causes infections such as pneumonia, meningitis, otitis media, and bacteremia. The prevention of pneumococcal disease by vaccination has become more urgent due to increased antibiotic resistance. Pneumococcal capsular polysaccharides (CPS) are effective vaccine antigens that stimulate the host to produce protective antibodies. S. pneumoniae serotype 14 is one of most prevalent types in Latin America and across the world. However, the yield of S. pneumoniae serotype 14 CPS from existing fermentation processes remains low and requires improvement. In this study, various aspects of the fermentation process were optimized to improve pneumococcal growth and polysaccharide productivity, including feed medium, cultivation gas environment, fermentation pH, and temperature. A simplified purification method was also developed to obtain pure CPS, including ultrafiltration, acid and ethanol precipitation, diafiltration, and lyophilization. These fermentation optimizations significantly enhanced the optical density of pneumococcal bacterial cultures and increased fermentation yields to 2.4–2.6 g/L—significantly higher than previously achieved. Furthermore, the test results of pure CPS could meet the requirements in the European Pharmacopoeia (11th edition). These optimizations provide valuable insights into the nutritional requirements and impact of varying fermentation process parameters on pneumococcal growth and CPS productivity, thus contributing to the development of a more efficient and cost-effective method for the production of pneumococcal CPS—essential for manufacturing vaccines against pneumococcal infections.